Species composition and diversity of mangrove communities associated with Lumnitzera littorea in Southern Vietnam - Quach Van Toan, Em; Vien Ngoc, Nam; Ngo, Xuan Quang (Academia Journal of Biology, 2025)
Mangroves are among the world’s most threatened ecosystems, with approximately 50% of the global mangrove area lost since 1900 and 35% lost in the past two decades. This study assessed the species composition and diversity of mangrove communities in southern Vietnam. Plant species were identified and measured using a plot method, with 10 m × 10 m plots established at three different sampling sites. A total of 15 plant species were recorded, including 13 true mangrove species and two associated species. Among these, Aegiceras floridum R. & Sch. is listed as Near Threatened by the IUCN, while Lumnitzera littorea is classified as Vulnerable in the Vietnam Red Data Book. In areas where L. littorea is dominant, diversity indices were low, with uneven species distribution across plots. The highest diversity was recorded on Con Dao Island, and the lowest on Phu Quoc Island. Our findings suggest that to conserve and protect high-diversity L. littorea communities, they should be planted together with Ceriops tagal or Rhizophora apiculata, given the high similarity coefficient (> 0.5) among these species.